Regional integration in a globally networked economy. - KORBIN, Stephen J. (1995)
Points out that the emerging globally integrated world economy is a reflection of fundamental changes in the scale and complexity of technology and the digitalization of international economic transactions. Notes that regional economic integration in the 1990s is the latest step in a century-long process of geographic expansion of markets from local, to national and now to international. Argues that (1) regional markets may not be large enough to support efficient production or competitive research and development efforts; (2) borders are losing meaning in an electronic age; and (3) geography is becoming less relevant as the basis for organising and controlling economic activity.